Efforts to Address Sexual Violence Against Girls with Disabilities - Ririn Wijayanti; Maya Shafira; Muhammad Farid; Diah Agustiniati; Refi Mediantama (Jurnal Ilmiah Hukum dan Hak Asasi Manusia, 2026)
Purpose: This study aims to examine the effectiveness of legal responses to sexual violence against girls with disabilities in Indonesia, identifying gaps in protection and enforcement. Methodology/approach: Employing a normative-empirical legal analysis, the research reviews positive law provisions namely the Child Protection Act (UU No. 35/2014 as amended), the Disability Act (UU No. 8/2016), and the Sexual Violence Criminal Act (UU No. 12/2022) and analyzes Supreme Court and lower court decisions. Empirical data were gathered through semi-structured interviews with law enforcement officers and observations of case handling in selected provincial offices. Results/findings: Despite a comprehensive statutory framework, implementation is hampered by limited officer training, inadequate facilities, and low public awareness. Criminal legal protection for girls with disabilities remains neither fully effective nor sufficiently inclusive, with procedural delays and accessibility barriers persisting. Limitations: The study is constrained by its qualitative focus on selected jurisdictions and does not include quantitative victim-survey data, which may limit generalizability across all regions of Indonesia. Contribution: Engagement this research informs policymakers, legal practitioners, and disability rights advocates on improving justice outcomes for one of Indonesia’s most vulnerable groups. Conclusion: Legal protection for girls with disabilities who are victims of sexual violence is regulated by several laws in Indonesia, but its implementation remains ineffective due to limited understanding among law enforcement, inadequate facilities, and low public awareness. The main obstacles include unintegrated regulations, insensitive law enforcement officers, and limited legal services.